Foundational Literacy and Numeracy Skills of Students of Nayagarh District of Odisha - Sathua, Madhusmita; Krishnan, Dhanya (JOURNAL OF INDIAN EDUCATION, 2024)
Considering the criticality of foundational literacy and numeracy skills in lifelong learning, this paper analyses the status of literacy and numeracy skills of Grade III students of Government schools of Nayagarh district of Odisha. The paper also analyses the literacy and numeracy skills of students with respect to gender, and examines the relationship between literacy and numeracy skills. The study employed a descriptive survey method. Data was collected from 105, Grade III students from schools of Nayagarh district, Odisha. For the analysis of data, descriptive statistics, i.e., mean, standard deviation, t-test, percentage, range and Pearson co-efficient of correlation were employed. Analysis showed that the level of foundational literacy is better in comparison to the level of foundational numeracy, however, the study also found that 19.04 per cent of students were unable to read. Result of the study also indicated that there is no considerable difference both in literacy and numeracy skills of students with respect to gender. The study identified a positive relationship between literacy and numeracy skills. The study recommends for innovative and interdisciplinary pedagogical strategies for the classrooms at foundational stage with due emphasis on different sub skills and components of foundational literacy numeracy.